Innovation and Competitive Strategy in Tech Start-Ups: Evidence from Emerging Markets - Thakre, Shital Vishnupant; Nath, Umesh Balkrishna; G. waghole, Vallabh; Bhalerao, Ajinkya Sanjay (Journal of Neonatal Surgery, 2024)
The emerging markets are transforming the economic environments at a very rapid rate due to the new tech start-ups that embrace the power of innovation as one of the key factors that contribute to competitive advantage. The research problem of the current research is the relationship between innovation practices and establishment of competitive strategy in tech start-ups operating in chosen emerging economies. The proposed study is aimed at exploring the functions of product innovation, process innovation, embracing digital, and strategic agility in maintaining the sustained competitiveness, according to the Resource-Based View (RBV) and Dynamic Capabilities Theory. Semi-structured interviews that complemented the survey (mixed-methodology approach) in 220 Indian, Brazilian, Indonesian, and South African tech start-ups provided more detailed explanations of qualitative information. The findings indicate that the magnitude of innovation has a significant impact on the differentiation of the market, reduced costs and the freedom of strategy. Besides this, ecology problems in the research paper also present issues like shortage of funds, regulations and lack of expertise that mediate the innovation strategy relationship in the emerging markets. The results show that the key element in strategic positioning is to create cultures of innovation, build digital capacity and effective stakeholder networks. The research will contribute to the existing literature on the phenomenon of innovation management in the newly opened markets and will generate viable implications to the founders, investment community, and policy-makers who are interested in encouraging sustainable development of the technological-innovation-based entrepreneurial ecosystems.